Comparison of the Effectiveness of Reality Therapy and Emotion-Focused Therapy on Self-Esteem and Communication Beliefs in Divorced Women - Souri, Fatemeh; Jahangiri, Mohammad Mehdi; Pirani, Zabih (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effectiveness of reality therapy and emotion-focused therapy on self-esteem and communication beliefs in divorced women living in Tehran.Methods and Materials: This study was applied in nature and used a semi-experimental design with pre-test, post-test, and follow-up measurements, alongside a control group. The statistical population of this research consisted of all divorced women residing in District 2 of Tehran in 2023. From this population, 45 individuals were selected using purposive sampling and then randomly assigned to two intervention groups (reality therapy and emotion-focused therapy) and one control group, ensuring age homogeneity. Participants completed a pre-test, post-test, and follow-up using the Communication Beliefs Questionnaire and the Self-Esteem Scale. The first intervention group received eight sessions of reality therapy, and the second intervention group received ten sessions of emotion-focused therapy, while the control group did not receive any intervention. Data were analyzed using repeated measures analysis of variance (ANOVA) and SPSS-22 software.Findings: The findings revealed that both reality therapy and emotion-focused therapy were effective in enhancing self-esteem in divorced women in Tehran, and the effects of both treatments were sustained over time. There was no significant difference between the effectiveness of reality therapy and emotion-focused therapy in improving self-esteem. Both therapies were also found to be effective in improving communication beliefs, with the effects being long-lasting. No significant difference was found between the effectiveness of reality therapy and emotion-focused therapy on communication beliefs.Conclusion: Based on the results, it can be concluded that both reality therapy and emotion-focused therapy are effective in improving self-esteem and communication beliefs in divorced women in Tehran.